2022
DOI: 10.1155/2022/1218128
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Breast Cancer Molecular Subtypes and Ki67 Expression as a Predictive Value for Pathological Complete Response following Neoadjuvant Chemotherapy: Experience from a Tertiary Care Center in Lebanon

Abstract: Introduction. Breast cancer is considered nowadays the most prevalent cancer worldwide. The molecular era has successfully divided breast cancer into subtypes based on the various hormonal receptors. These molecular subtypes play a major role in determining the neoadjuvant chemotherapy to be administered. It was noted that the use of neoadjuvant chemotherapy was associated with higher achievement of pathological complete response. The aim of the study was to determine the predictive role of breast cancer subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Breast cancer (BC) is the most pernicious type of cancer and has been ascribed as the second most prime cause of premature mortality among women. Around 1.5 million women (20–59 years) throughout the world and in the Middle East part of the globe are being the victims of this cancer in each year as per global cancer project (GLOBOCAN 2012). , Of note, it has been observed that the female in less developed and in industry-based countries encounters the most common non-dermatologic malignancy, and thus, it has been unveiled as a second vital reason of mortality in the United States and in Europe after lung cancer. , The steady increase in global encumbrance of BC in all ethnicities can be assumed to prevail due to the exogenous factors like lifestyle, reproductive factors, and genetic factors like mutations occurring in breast cancer susceptibility gene 1 (BRCA1) and breast cancer susceptibility gene 2 (BRCA2), manifesting the tumors with more hostile phenotypes and thereby playing a significant role in the etiology of such cancer . The high body mass index (BMI), family history of ovarian or breast cancer, nulliparity or first birth at age greater than 30, late menopause, and postmenopausal hormone therapy can be included as the other most important risk factors of breast cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer (BC) is the most pernicious type of cancer and has been ascribed as the second most prime cause of premature mortality among women. Around 1.5 million women (20–59 years) throughout the world and in the Middle East part of the globe are being the victims of this cancer in each year as per global cancer project (GLOBOCAN 2012). , Of note, it has been observed that the female in less developed and in industry-based countries encounters the most common non-dermatologic malignancy, and thus, it has been unveiled as a second vital reason of mortality in the United States and in Europe after lung cancer. , The steady increase in global encumbrance of BC in all ethnicities can be assumed to prevail due to the exogenous factors like lifestyle, reproductive factors, and genetic factors like mutations occurring in breast cancer susceptibility gene 1 (BRCA1) and breast cancer susceptibility gene 2 (BRCA2), manifesting the tumors with more hostile phenotypes and thereby playing a significant role in the etiology of such cancer . The high body mass index (BMI), family history of ovarian or breast cancer, nulliparity or first birth at age greater than 30, late menopause, and postmenopausal hormone therapy can be included as the other most important risk factors of breast cancer .…”
Section: Introductionmentioning
confidence: 99%